Prediksi Nilai Tukar Dollar (USD) ke Rupiah (IDR) menggunakan Artificial Neural Network - Saparudin, Ahmad; Maulidina, Tiya (Prodi Sistem Informasi FST Universitas Jambi, 2019)
Prediction (forecasting) is the activity of predicting events in the future. In terms of business forecasting has many uses, especially for the leadership of the company one of them i.e. to define its business strategy in the future. In this research, carried out the predictions of exchange rates dollar (USD) to Indonesian rupiah (IDR) on 11/03/2019 - 15/03/2019 using artificial neural networks (ANN) with a training dataset from 01/01/2018 - 08/03/2019. Establishment of ANN in the study formed in the Python programming language. Based on the research conducted, a decrease in the price of the exchange rate of USD to IDR on 11/03/2019 – 15/03/2019.